2017
DOI: 10.3855/jidc.7612
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular and soft-tissue melioidosis in Malaysia: clinical characteristics and molecular typing of the causative agent

Abstract: Introduction: Melioidosis involving bone, joints, and soft tissue is rare and reported usually following dissemination of disease from infection elsewhere in the body; to a lesser degree, it can also be reported as the primary manifestation of melioidosis. Methodology: The orthopedic registry at Hospital University Sains Malaysia from 2008 until 2014 was retrospectively reviewed and was followed by molecular typing of Burkholderia pseudomallei. Results: Out of 20 cases identified, 19 patients were confirmed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…Various studies have reported human infections by B . thailandensis belonging to both cluster I (ST77, ST80 and ST345) and cluster II (ST73 and ST101) (https://pubmlst.org/bpseudomallei/) [510]. It has been postulated that B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have reported human infections by B . thailandensis belonging to both cluster I (ST77, ST80 and ST345) and cluster II (ST73 and ST101) (https://pubmlst.org/bpseudomallei/) [510]. It has been postulated that B .…”
Section: Resultsmentioning
confidence: 99%
“…thailandensis is a member of the B . pseudomallei complex, is considered a-virulent [3,4] and rarely causes disease in humans [510]. Knowledge about the global distribution of B .…”
Section: Introductionmentioning
confidence: 99%
“…Even the possibility of co-infection of melioidosis and TB was not suspected. B. pseudomallei is well known to cause latent infection [17], although it is not documented that whether the anti-tubercular treatment has any effect in suppressing the bacteria Bone and joint involvements like septic arthritis and osteomyelitis are very well-documented clinical presentations in melioidosis [18], whereas pulmonary involvement was more commonly observed in TB. The extra-pulmonary involvement is more common in melioidosis than TB and less challenging in diagnosis, still it is missed most often [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic medication used should have a good penetration into the brain tissue as well as activity against B. pseudomallei . The drug of choice for the treatment of melioidosis are ceftazidime or meropenem, alone or with SXT [16].…”
Section: Discussionmentioning
confidence: 99%